(untitled) (Research, Society and Development, 2021)
Aim: The present study aimed to verify whether the consumption of higher doses of whey proteins present changes in liver biomarkers and in the feed intake in sedentary Wistar rats compared to lower doses. Materials and Methods: This is an experimental study, the study was carried out with 32 rats that were allocated in four groups: C - non-supplemented control (n = 10), S2 - supplemented with 2g/kg/day (n = 10), S4 - supplemented with 4g/kg/day (n = 7), S6 - supplemented with 6g/kg/day (n = 5) by gavage and supplemented with whey proteins. Bilirubin and Albumin biomarkers will be analyzed. Results: Regarding total proteins, significant differences were found between groups C and W6 (p = 0.0282) and between groups W2 and W6 (p = 0.0054). For Bilirubin significant differences were found only between groups W2 and W6 (p = 0.0213). Main Conclusions: The findings of this study suggest that doses of 2, 4 and 6g/kg/day of whey proteins do not influence the alteration of liver biomarkers, constituting a hepatoprotective supplement and as the dosage of supplementation increases, there is a reduction in feed consumption, suggesting that whey protein supplementation may regulate rat food intake.